Volatile organic compounds released by the entomopathogenic fungus Beauveria bassiana - Crespo, Rosana (2008)
The composition of volatile organic compounds (VOC) released by the entomopathogenic fungus Beauveria bassiana (Hyphomycete: Deuteromycotina) utilizing two different carbon sources was investigated. Analyses were performed by solid-phase microextraction (SPME) coupled to capillary gas chromatography (CGC) and CGC-mass spectrometry (MS). Major components in glucose-grown cultures were diisopropyl naphthalenes, ethanol, and sesquiterpenes. Alkane-grown fungal VOC switched to a fingerprint with prevalence of n-decane. This is the first report on the volatiles released by entomopathogenic fungi.